Hubungan Senioritas Dan Budaya Kerja Dengan Organizational Citizenship Behaviour Pada Personel Satuan Brigade Mobile Polisi Daerah Sumatera Utara - Nazly Fadhilah Manurung; Muhammad Rajab Lubis; Sjahril Effendy (Universitas Medan Area, 2021)
The success of an institution cannot be separated from its HR factor. The superior quality of the personality of HR in an institution becomes its own pride and also becomes a weapon to advance an institution. Likewise in the Police environment, superior human resources are key in advancing POLRI institutions. The phenomenon that occurs at the current research site is that there are still many cases of disciplinary violations committed by members of the North Sumatra Regional BRIMOB. OCB is believed to contribute more in the workplace. Purpose of this study was to determine the relationship between seniority and work culture on OCB. The population in this study was the North Sumatra Regional BRIMOB personnel serving in Medan, amounting to 752 personnel, then taken as many as 120 research samples, sampling taken random sampling. This is a quantitative research. Data collection uses a scale from OCB, Seniority and Work Culture. This research tested using multiple regression analysis. The results showed a) a positive and strong relationship between Seniority and OCB with a correlation coefficient value rx1y = 0.557 and Seniority contributed 31%, b) a positive and moderate relationship between Work Culture and Organizational citizenship behavior with a correlation coefficient of rx2y = 0.485 and Work Culture contributes 23.5%, c) there is a positive and strong relationship between Seniority and Work Culture with OCB with correlation coefficient rx1x2y = 0.589, so it can be concluded that Seniority and Work Culture contribute equally by 34.6% against OCB. Based on these results, the three hypotheses in this study were accepted.